2018
DOI: 10.1177/1464884918781794
|View full text |Cite
|
Sign up to set email alerts
|

‘Friends call me racist’: Experiences of repercussions from writing comments on newspaper websites

Abstract: Based on a survey among contributors to the online comments sections of four Norwegian newspapers, we investigate the following research question: How do contributors describe their experiences of repercussions from writing comments on newspaper websites? Employing quantitative and qualitative analyses, we explore the influence of four variables: Gender, anonymity, attitudes towards editorial policies and issue controversy. We find no influence from gender. However, regarding attitudes we find that the experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…Based on the analysis elaborated below, I suggest that one of these dynamics can be affective discipline, where participants of a discussion take action against other participants' behaviour in ways that intervene in the mood of the discussion and direct its attunement (cf. Langlois et al, 2009;Løvlie et al, 2018;Tong, 2017: 412, 414).…”
Section: Affect In Online Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis elaborated below, I suggest that one of these dynamics can be affective discipline, where participants of a discussion take action against other participants' behaviour in ways that intervene in the mood of the discussion and direct its attunement (cf. Langlois et al, 2009;Løvlie et al, 2018;Tong, 2017: 412, 414).…”
Section: Affect In Online Discussionmentioning
confidence: 99%
“…As Ziegele et al (2017) and Løvlie et al (2018) note, news containing news values, such as controversy and damage appear to encourage active online commenting, even though the covered events are not in an area of cultural or geographical proximity to the commenters (see also Larsson, 2018b). In other words, controversial or disruptive topics appear to have more affective stickiness (Ahmed, 2004) that can carry on over time, and they therefore invite and sustain more attention and engagement (Paasonen, 2015) than other topics.…”
Section: Materials and Historical Contextsmentioning
confidence: 99%
“…Scientific research has empirically demonstrate it (Coe, Kenski & Rains, 2014). Løvlie, Ihlebaek and Larsson (2018) stated the experience of commenting is particularly meaningful for those whom oppose to a specific media outlet. Santana (2015) concluded that negative discourses in these spaces tend to increase towards immigration issues, based on a survey at sites of three online newspapers in Border States.…”
Section: Media Producers and Journalists' Perceptions On Interactivitymentioning
confidence: 99%
“…The news media can in other words be an arena for inclusion and solidarity based on mediated emotional connections, but they can also represent a space of conflict and exclusion (Orgeret, 2020). One of the ways in which audiences can respond to journalism is by participating in comment sections (Ihlebæk and Krumsvik, 2015; Løvlie et al, 2018a; Lünenborg and Maier, 2018; Toepfl and Piwoni, 2015). Several studies have indicated how such spaces have become arenas for incivility and hate (Coe et al, 2014; Erjavec and Kovacic, 2012; Quandt, 2018; Su et al, 2018; Waldron, 2012), how participation can be triggered by anger (Springer et al, 2015; Wollebæk et al, 2019; Ziegele et al, 2017) and how journalists have responded to this kind of audience participation (Canter, 2013; Frischlich et al, 2019; Lewis, 2012; Singer et al, 2011; Bergstrom and Wadbring, 2015).…”
Section: Introductionmentioning
confidence: 99%